1997
DOI: 10.1093/jat/21.5.376
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Thebaine in Urine for the Detection of Poppy Seed Consumption

Abstract: The consumption of poppy seeds in various foods may lead to a positive opiate result in urine subjected to testing for drugs of abuse. As a natural constituent of poppy seeds, thebaine was investigated as a possible marker for poppy seed consumption. Poppy seeds were examined for opiate content by gas chromatography-ion trap mass spectrometry (GC-MS) after extraction with methanol. Urine samples spiked with thebaine and urine from subjects given 11 g of poppy seeds were tested for the presence of thebaine, cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Cassella et al [13] reported positive results, while ElSohly et al [12] reported negative ones. Also at variance were reports on the amenability of thebaine to trimethylsilyl (TMS) derivatization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cassella et al [13] reported positive results, while ElSohly et al [12] reported negative ones. Also at variance were reports on the amenability of thebaine to trimethylsilyl (TMS) derivatization.…”
Section: Introductionmentioning
confidence: 99%
“…Thebaine (Fig. 1), a constituent of both opium and poppy seeds, had been suggested as a urinary marker to differentiate between heroin use and the use of poppy seed-containing foods [12][13][14][15][16], which are common in North America and western European countries. Because thebaine is present at much higher concentrations in opium (0.1-2.5% w/w) [17] than in the poppy seeds (0.00003-0.0014% w/w) [12], it should be targeted as a marker of opium use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include reticuline [11], neopine [12], and thebaine for opium, and 6-monoacetylmorphine (6-MAM) [14] and acetylcodeine [15] for heroin. Thebaine has been recommended as a marker of poppy seed ingestion in differentiation from heroin use [16], and because it is present in a much higher content in opium than in poppy seeds, it can be also used as a marker of opium ingestion. In differentiation between opium use and illicit heroin use, when the latter cannot be confi rmed through the detection of 6-MAM and/or acetylcodeine because of their very narrow windows of detection [14,15], a marker inclusion/exclusion approach is recommended.…”
Section: Resultsmentioning
confidence: 99%
“…There are also other methods described in the literature, such as oxidative colorimetric analysis [22], determination of opiates by circular dichroism [23], colorimetric determination [24], TLC analysis of opiate alkaloids and drugs [25,26], ELISA (enzyme-linked immunosorbent assay) analysis of thebaine [27], FTIR spectroscopy of opiates and chemometric analysis [28], differential pulse polarography [29] and even a voltammetric analysis of thebaine [30]. (6) and noscapine (7) T a b l e 2 [31], gas chromatography-ion trap mass spectrometry (GC-MS) analysis [32], liquid chromatographicatmospheric pressure chemical ionization mass spectrometric analysis [33] or HPLC analysis [34,35], GC-MS analysis [36][37][38][39]. Alkaloids are also being analyzed in environmental studies to trace the pollution of the environment [40].…”
Section: Introductionmentioning
confidence: 99%